Active metamaterials : terahertz modulators and detectors - Rout, Saroj; Sonkusale, Sameer (Springer, 2017)
This book covers the theoretical background and experimental methods for engineers and physicist to be able to design, fabricate and characterize terahertz devices using metamaterials. Devices utilize mainstream semiconductor foundry processes to make them for communication and imaging applications. This book will provide engineers and physicists a comprehensive reference to construct such devices with general background in circuits and electromagnetics. The authors describe the design and construction of electromagnetic (EM) devices for terahertz frequencies (108-1010cycles/sec) by embedding solid state electronic devices into artificial metamaterials where each unit cell is only a fraction of the wavelength of the incident EM wave. The net effect is an electronically tunable bulk properties with effective electric (permittivity) and magnetic (permeability) that can be utilized to make novel devices to fill the terahertz gap.
Keywords: Metamaterials.; Terahertz technology.; Wireless communication systems.; elektronické knihy; electronic books